Tradisi Upacara Peutren Aneuk pada Masyarakat Aceh Barat: Proses, Makna dan Nilai - Reva Riana; Iromi Ilham; Teuku Kemal Fasya; Rizki Yunanda (Aceh Anthropological Journal, 2023)
This article aims to discuss how the process of carrying out the peutren aneuk ritual (getting off the ground ceremony) in the people of West Aceh and analyze the meaning and values contained in this traditional ceremony. This discussion is important as an effort to transmit knowledge and educational facilities to the younger generation so that local ritual traditions and local wisdom can be maintained and continue to be passed down. The research method used is qualitative with three data collection techniques, namely participatory observation, interviews and document study. The process of data analysis includes the stages of data reduction, data presentation and drawing conclusions. The results of the study show that the tradition of the peutren aneuk ceremony in the people of West Aceh is carried out as a form of respect and gratitude to Allah SWT for the birth of a baby. The peutren aneuk ritual tradition is carried out when the baby is 7 to 44 days old. The process of the peutren aneuk ritual ceremony includes peusijuk, peucicap, turning chicken hearts, cuko 'ok, splitting a coconut, peugideung tanoh, bringing it to the mosque, silat (if you have a vow), reciting the Koran, samadiah, and reciting the barzanji. While the meaning and value of the whole process of carrying out the ceremony can be interpreted from three symbolic dimensions, namely speech, behavior, and the objects used. For example, speech symbols are present in the form of narrative poems that contain good advice and prayers.Abstrak: Artikel ini bertujuan untuk membahas bagaimana proses pelaksanaan ritual peutren aneuk (upacara turun tanah) pada masyarakat Aceh Barat serta menganalisis makna dan nilai yang terkandung dalam upacara adat tersebut. Pembahasan ini penting dilakukan sebagai salah satu upaya transmisi pengetahuan dan sarana edukasi kepada generasi muda agar tradisi ritual dan kearifan lokal setempat dapat terjaga dan terus diwariskan. Metode penelitian yang digunakan adalah kualitatif dengan tiga teknik pengumpulan data, yaitu observasi partisipatif, wawancara dan studi dokumen. Proses analisis data mencakup tahapan reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa tradisi upacara ritual peutren aneuk dalam masyarakat Aceh Barat dilaksanakan sebagai bentuk penghormatan dan rasa syukur kepada Allah SWT atas kelahiran bayi. Tradisi upacara ritual peutren aneuk dilakukan dalam rentan waktu bayi berumur 7 sampai 44 hari. Proses upacara ritual peutren aneuk meliputi peusijuk, peucicap, membolak-balik hati ayam, cuko ’ok, membelah kelapa, peugideng tanoh, membawa ke masjid, silat (jika memiliki nazar), mengaji, samadiah, dan membaca berzanji. Sementara makna dan nilai dari segenap proses pelaksanaan upacara dapat ditafsirkan dari tiga dimensi simbolik, yaitu ucapan, perilaku, dan benda-benda yang digunakan. Misalnya, simbol ucapan hadir dalam bentuk penuturan syair-syair yang berisi nasehat dan doa kebaikan.